Perceived Similarity as the Source of the Feeling of Intergroup Threat: Testing the Brown’s (1984) Hypothesis in the Cameroonian Linguistic Context - Messanga, Gustave Adolphe (Journal of Advanced Research in Social Sciences, 2021)
In Cameroon, a country which has undergone a double French/British administration (1916-1961), the cohabitation between Francophones and Anglophones since 1961 is far from having erased the intergroup differences linked to their respective colonial pasts. On the contrary, over time, it has generated what has been called the Anglophone problem. In this context, is the strong tendency towards the schooling of students from francophone families in schools of the anglophone sub-system of education likely to attenuate intergroups cleavages? From the theoretical perspective of social identity, this research suggests that the perceived similarity between Anglophones and anglophonized francophones generates a threat to the specific Anglophones' linguistic identity. To test this hypothesis, the optimal distinctiveness and intergroup threat scales were administered to 462 Anglophones participants of both sexes. The correlation and linear regression analyzes provide empirical support for the hypothesis of the study. An adjusted R2 index validates the existence of a causal relationship between perceived similarity and intergroup threat.